EFEKTIVITAS PENYULUHAN METODE SEKOLAH LAPANG TERHADAP PENERAPAN STANDAR OPERASIONAL PROSEDUR (SOP) BUDIDAYA ANGGREK TANAH (TERESTRIAL) DI KOTA TANGERANG SELATAN - Hendrik Hexa; Ujang Maman; Junaidi J (Departement of Agribusiness Faculty of Science and Technology, 2017)
Orchid is one of floricultural crops that spreads widely throughout the world. This plant is popular because of its beauty with the variety of shapes and colors. Types of orchid that widely used as a cut flower are terrestrial orchids because these kinds of orchid have the long and strong stalks, a lot of buds, attractive shapes and colors, and long shelf life. The Field School of floricultural plant GAP-SOP (Good Agricultural Practices - Standard operational procedure) is an approach by using adult learning methods in enhancing the farmers’ knowledge, abilities, and skills in applying the principles of GAP (Good Agricultural Practices) floricultural plants through experiential learning, by using a land as the place to learn, monitoring regularly in a week or two weeks throughout the growing season, examining and discussing so that the farmers can understand and make their own decisions. The data analysis methods use Chi-Square (X2) that used to determine the relationship between the knowledge of orchid farmers that study in the field schools with the standard implementation of operational procedures of orchid cultivation in the city of South Tangerang. According the analysis of X2, between farmers' knowledge and the implementation in the SOP (Standard operational procedure) of terrestrial orchid cultivation by farmers, it obtains the results 14.273 of X2 count and 0.006 P-value. The results show there is a relationship between the knowledge and the implementation in the SOP of terrestrial orchid cultivation because the count value of X2 is greater than the table of X2 value (14.273> 9.488) and the P-value is less than the critical limit (0.006 <0.05). Knowledge authentically relates to the farmers application-level, the more knowledge level of the farmers, the higher of implementation level in the SOP of terrestrial orchid cultivation by farmers. Councelling effectiveness level of the Field School methods is on the criteria of median (quite effective).